2014
DOI: 10.1021/ac4031779
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Spray Ionization Mass Spectrometry Imaging

Abstract: Imaging samples on a surface by mass spectrometry (MS) requires the combination of MS detection with a scanning mode that enables localized desorption and ionization and/or detection of sample analytes with good spatial resolution. We have developed a new mass spectrometry imaging (MSI) method based on electrostatic spray ionization. It works under ambient conditions and can be applied to a wide range of molecules providing quantitative MS analysis even in the presence of salts in excess. 2D MS images of prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Since then, a number of other ambient MSI modalities have also been developed that utilize different ambient ionization techniques to create MS images. The variety of methods include laser-based techniques such as laser ablation electrospray ionization (LAESI) MS [15] and transmission geometry laser ablation MSI [16], spray-based techniques such as DESI MS and electrostatic spray ionization (ESTASI) MS [17], and surface micro-extraction-based methods such as LMJ-SSP MS [18], liquid extraction surface analysis (LESA) MS [19], and nano-DESI MS [20], among many other emerging technologies that are actively being researched at the present time [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, a number of other ambient MSI modalities have also been developed that utilize different ambient ionization techniques to create MS images. The variety of methods include laser-based techniques such as laser ablation electrospray ionization (LAESI) MS [15] and transmission geometry laser ablation MSI [16], spray-based techniques such as DESI MS and electrostatic spray ionization (ESTASI) MS [17], and surface micro-extraction-based methods such as LMJ-SSP MS [18], liquid extraction surface analysis (LESA) MS [19], and nano-DESI MS [20], among many other emerging technologies that are actively being researched at the present time [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, DESI has some drawbacks, including low sensitivity and low ionization efficiency compared with surface extraction-based techniques, which can limit its applications [11]. ESTASI MS uses a high voltage to create localized spray of ions from the sample surface that has been able to achieve a resolution of 200 μm on cell culture samples [17]. Surface micro-extraction techniques, in general, allow a greater efficiency of analyte extraction than spray-based techniques because of a greater efficiency of analyte transfer from the sample to the MS, as has been demonstrated previously where surface digested proteins analyzed with LESA MS were able to give better sensitivity and protein identification than DESI MS [23].…”
Section: Introductionmentioning
confidence: 99%
“…4 and 3(a) demonstrated that 2D ESTASI-MSI is a powerful method to reveal completely and accurately the spatial distribution of the analytes separated by TLC. Compared with the images obtained previously, 7 the image resolution and integrity have been improved signicantly, which could be contributed to the hydrophobic-hydrophobic or hydrophilic-hydrophilic interactions between samples and TLC substrates leading to a reduced tailing effect.…”
mentioning
confidence: 79%
“…3(a) with a protocol described in detail in a recent publication. 7 The same extraction solvent was used, and the motored travel stage was moved in both x and y directions with the step size of 200 mm, the translation rate of 5 mm s À1 and the delay time of 1 s to accomplish the 2D scan. Normalized Rel.…”
mentioning
confidence: 99%
“…[43,44] Micro-3D-patterns and test samples for scanning electrochemical microscopy and electrostatic spray ionization massspectrometry imaging have been prepared as well. [45,46] Furthermore, inkjet printing has been employed in LEPA to create CLs and MEAs for PEMFCs. Similar to the works reported by the groups of Taylor, [37] Towne, [38] Karan [39] and Secanell [40] stable ink formulations of Pt/C inks with Nafion (Fig.…”
Section: Inkjet Printing Of Electrocatalystsmentioning
confidence: 99%